"You Have to Cry Before You Teach This Class": Emotion With Work and Resistance in Teaching Intercultural Communication - Brandi Lawless; Yea-Wen Chen (Central States Communication Association, 2019)
In this study, we explore the ways in which Intercultural Communication instructors uniquely experience emotion with work and how this influences their pedagogical approaches to this course. We collected and analyzed interviews with 21 intercultural communication educators across U.S. colleges and universities. We present findings related to the types of resistance present and/or emerging in the intercultural communication classroom, emotional responses to resistance, and strategies for managing and negotiating emotion with work in the Intercultural Communication classroom. We end with discussing implications for teacher training programs designed for the Intercultural Communication classroom.